Effect of Bilateral Subthalamic Nucleus Deep Brain Stimulation on Pisa Syndrome in Parkinson's Disease - He, Jing; Cui, Zhuang; Li, Shuhua; Chen, Haibo; Su, Wen (Frontiers in Neurology, 2021)
Objective: To observe the efficacy of bilateral subthalamic nucleus deep brain stimulation on Pisa syndrome in patients with Parkinson's disease. Methods: A total of 52 patients with Parkinson's disease who underwent deep brain stimulation in Beijing Hospital from July 1, 2016 to July 1, 2020 were reviewed. The clinical data were collected for the patients who met the diagnostic criteria of Pisa syndrome on “Medication-Off” state pre-operatively. Results: Two patients met the diagnostic criteria of Pisa syndrome before operation, with a Pisa angle of 10 and 14°, respectively. The lateral trunk flexion of the two patients improved after operation. In stimulation-on/medication-off state, the Pisa angle decreased from 10 to 2° and from 14 to 6°, respectively. Conclusion: Bilateral subthalamic nucleus deep brain stimulation might have beneficial effects on lateral trunk flexion in PD patients, but the predictors of curative effect are not clear.